2014
DOI: 10.1103/physrevb.90.214103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vegard strains on the extrinsic size effects in ferroelectric nanoparticles

Abstract: By changing the size and the shape of ferroelectric nanoparticles, one can govern their polar properties including their improvements in comparison with the bulk prototypes. At that the shift of the ferroelectric transition temperature can reach as much as hundreds of Kelvins. Phenomenological description of these effects was proposed in the framework of Landau-Ginsburg-Devonshire (LGD) theory using the conceptions of surface tension and surface bond contraction. However, this description contains a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…[34]. In particular depolarization field always decreases ferroelectric polarization and transition temperature.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[34]. In particular depolarization field always decreases ferroelectric polarization and transition temperature.…”
Section: Introductionmentioning
confidence: 90%
“…Note, that an additional size dependence of the Curie temperature shift in comparison with a bulk value is possible due to the excess surface stress [29,34], flexoelectric strains and chemical pressure mechanism [41]. Namely,…”
Section: B Analytical Solution For a Single-domain Casementioning
confidence: 99%
“…Such study may be very useful for science and advanced applications, because the theory of finite size effects in nanoparticles allows one to establish the physical origin of the polar and other physical properties anomalies, transition temperature and phase diagrams changes appeared with the nanoparticles sizes decrease. In particular, using the continual phenomenological approach Niepce [52], Huang et al [53,54], Ma [55], Eliseev et al [56] and Morozovska et al [57,58,59,60,61] have shown, that the changes of the transition temperatures, the enhancement or weakening of polar properties in spherical and cylindrical nanoparticles are conditioned by the various physical mechanisms, such as correlation effect, depolarization field, flexoelectricity, electrostriction, surface tension and Vegardtype chemical pressure.…”
Section: Multiferroelectric Nanoparticles State-of-artmentioning
confidence: 99%
“…It is considered that the size effects are associated either with intrinsic (mainly related to the atomic polarization) or extrinsic (stresses, microstructure, polarization screening etc.) factors [57][58][59][60]. Semi-ellipsoid height is c and lateral semi-axes are a and b.…”
Section: Problem Statementmentioning
confidence: 99%
“…1b, which is consistent with Vagard's law. [23][24][25] Li + ions are expected to replace K + and Lu 3+ ions, which leads to lattice shrinking. When the doped concentration increases, the confusion trend of the cell volume could suggest the occupying of the interstitial sites of host matrix.…”
mentioning
confidence: 99%